PERANAN MAKRO-EKONOMI PADA SITUASI STATUS QUO PASCA KERUNTUHAN ANTAR MASA KEPEMIMPINAN INDONESIA DALAM PRESPEKTIF EKONOMI KELEMBAGAAN - Wira Ganet Aribowo (Universitas Merdeka Madiun, 2023)
The economic crisis is one of the triggers for economic crises in various countries from time to time. It's not just the economic crisis, apart from that, the more important thing is the collapse of the structure of society, the direction of the economy and politics in the future, in the status quo situation after the collapse between leadership periods in Indonesia, where government product regulations, including external institutions, cause uncontrolled public reactions to the transition situation. This article discusses the situation in Indonesia from era to era, from a macro-economic, political and institutional perspective. So economics and politics are a forum for leaders to decide on strategic policies in leading the government during the transition period.